Verification of selected electron beam induced current (EBIC) techniques - Ang, Alex Yong Guan (2008)
The diffusion lengths of materials within semiconductor devices have a very strong impact on device performance. Therefore, there is a need to establish a method that is capable of determining the diffusion length accurately within a semiconductor device. By using the scanning electron microscope (SEM) operating in the electron beam-induced current (EBIC) mode.